Perbandingan Nilai Intersepsi Pohon Mahoni (Swietania mahagoni) dan Pohon Pinus (Casuarina cunninghamia) - Siti Mechram; Susi Chairani; Ahmad Zaki (Department of Agricultural Engineering, Syiah Kuala University, 2012)
Comparation of Interception Loss on Mahoni (Swietania mahagoni) and Pinus (Casuarina cunninghamia)ABSTRACT. Interception of rain is the retention of rainwater on surface vegetation before it evaporates back into the atmosphere. Research relating to the interception is still lacking, so it is necessary to study the interception on some types of plants. Although the interception had a little value, and sometimes overlooked, but in some plants have a considerable effect. The purpose of this study was to determine the magnitude of interception in Mahogany and Pine trees, as well as to determine the relationship between rainfall and interception. In this study, samples taken at the Mahogany and Pine trees by the number of 3 samples of each tree. There were two approaches to measure the amount of interception, the first approach was the Volume Balance Approach and the second approach was the Energy Balance Approach. In this study, the volume balance approach, with measurements of rainfall, throughfall, stemflow and interception for ten days of rainfall. The average amount of interception Mahogany obtained 15.5 mm (7.31%) of the total amount of rainfall and the correlation coefficient (r) was at 0.554. While the average number of interception Pinus acquired 87.23 mm (41.15%) of the total amount of rainfall and the correlation coefficient (r) was at 0.505. The size of the interception was influenced by wind speed, density and canopy shape. The research obtained that the interception for pine trees was higher than Mahogany trees. The results also showed that the higher percentage of rainfall, the smaller interception. This was due to the canopy conditions and climatic factors.